«A cidade cresceu, a minha roça virou quintal»* - Ludivine Eloy (Cahiers des Amériques Latines)
This paper presents the results of the analysis of São Gabriel da Cachoeira’s agrarian system. This growing little town of North-West Amazonia (Alto Rio Negro) is surrounded by Indigenous Lands which face a low deforestation level. The urban population is mostly indigenous and still practice the manual slash-and-burn cultivation of bitter manioc. The families practice various production systems, which are frequently adapted to the urban market and are coping with urban constraint; their choices depend mostly on their migratory trajectories and on the acess to land. The periurban space is characterized by a mosaic of zones, with differenciations in terms of various land-use systems, landscape unities and land-tenure. Individual proprety is common, on the contrary to what it is in the Indigenous Lands. The families take advantage of the complementarity between farming and urban activities, which is revealed by the high mobility and the multilocal settlement and production paterns. Therefore, the analysis of these diferent familial strategies has to depart from the ideas of rural exode and dichotomal separation between rural and urban zone, in order to better seize the future of this region and to provide means to garanty the sustenability of this agriculture, which is a fundamental support of the regional indigenous culture.